Postoperative infection in foot & ankle surgery - Ashish Shah MD (Foot & Ankle Orthopaedics, 2018)
Category: Other Introduction/Purpose: Surgical site infections (SSI) are infections of the incision site, organ, or space at or near the surgical incision within 30 days of the procedure or within 90 days for prosthetic implants. Being the most common nosocomial infection, SSI’s are a burden to the healthcare system as they increase costs, duration of stay, antimicrobial resistance, morbidity, and mortality. While there is limited evidence in the orthopaedic literature suggesting that the incidence of SSI increases during the summer months, this association has not been examined in the setting of foot and ankle surgery. The purpose of this study was to determine whether seasonal variation plays a role in developing SSI’s after orthopaedic foot and ankle surgery. Methods: Data from the National Surgical Quality Improvement Program (NSQIP) years 2011-2015 were used in this study. The pooled and individual incidences of superficial incisional SSI, deep SSI, and organ space SSI were calculated and stratified by quarter of admission. The quarters of admission represent the various seasons (1=winter, 2=spring, 3=summer, 4=fall). Differences in the incidence of SSI as well as various demographic, comorbidity, and complication variables were evaluated using ANOVA for continuous variables and Pearson’s Chi-Square for categorical variables. Results: A total of 17,939 patients were identified. After pooling the superficial, deep, and organ space infections, the overall SSI rate was highest in the summer months (July-September, 3rd quarter) at 2.68% as compared to 2.20%, 2.33%, and 2.14% in the other respective quarters (p=0.338). There was a total of 218 cases of superficial incisional SSI. The summer months had the highest incidence of superficial SSI at 1.38% compared to 1.14%, 1.13%, and 1.21% for 1st, 2nd, and 4th quarters, respectively (p=0.677). There were 145 cases of deep incisional SSI. The third quarter again had the highest rate at 1.02% compared to 0.72%, 0.93%, and 0.60% for 1st, 2nd, and 4th quarter respectively (p=0.105). Conclusion: Our results show that superficial incisional SSI, deep incisional SSI, and open wound infections have increased likelihood during the summer months in the setting of orthopaedic foot and ankle surgery. Some studies have associated the increased temperature and humidity during the summer months with increased rates of infections and our results show similar trends. Additional evidence with larger sample sizes is needed to determine which specific procedures are at highest risk of infection during the summer months.